PENGEMBANGAN E-MODUL BERBASIS LITERASI SAINS IPAS MATERI HARMONI DALAM EKOSITEM DI KELAS V SDN 11 SITIUNG - Raimon Efendi; Eka Filahanasari; Muhammad Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is motivated by a module that does not yet reflect differentiated learning, which refers to learning that is adapted to students' learning styles, such as audio, visual and kinesthetic. An effort to overcome this problem is to innovate learning by utilizing digital technology to create teaching materials in the form of science literacy-based teaching e-modules using a books creator, which can be accessed and operated easily to improve the quality of learning. This type of research is research and development which uses the ADDIE development model. The trial was carried out on class V homeroom teachers at SDN 11 Sitiung with data collection techniques through analysis of validity test data, practicality of the E-Module. The resulting e-module obtained media, material and language validation scores with an average score of 89%, categorized as very valid. The practicality of the teaching e-module received a score of 94% which was categorized as very practical. So it can be concluded that the E-Module based on science and science literacy on harmony in ecosystems in class V at SDN 11 Sitiung is interesting and suitable for application and can continue to be developed as a learning innovation.